Ligands of CD6: roles in the pathogenesis and treatment of cancer - Gurrea-Rubio, Mikel; Lin, Feng; Wicha, Max S.; Mao-Draayer, Yang; Fox, David A. (Frontiers in Immunology, 2025)
Cluster of Differentiation 6 (CD6), an established marker of T cells, has multiple and complex functions in regulation of T cell activation and proliferation, and in adhesion of T cells to antigen-presenting cells and epithelial cells in various organs and tissues. Early studies on CD6 demonstrated its role in mediating cell-cell interactions through its first ligand to be identified, CD166/ALCAM. The observation of CD6-dependent functions of T cells that could not be explained by interactions with CD166/ALCAM led to discovery of a second ligand, CD318/CDCP1. An additional cell surface molecule (CD44) is being studied as a potential third ligand of CD6. CD166, CD318, and CD44 are widely expressed by both differentiated cancer cells and cancer stem-like cells, and the level of their expression generally correlates with poor prognosis and increased metastatic potential. Therefore, there has been an increased focus on understanding how CD6 interacts with its ligands in the context of cancer biology and cancer immunotherapy. In this review, we assess the roles of these CD6 ligands in both the pathogenesis and treatment of cancer.